KESANTUNAN BERBAHASA DALAM KOMENTAR EKSPRESIF PENGGUNA INSTAGRAM: STUDI KASUS KORUPSI PERTAMINA PADA AKUN IG @MEDANTALK - Christopher Goldwin Millardo; Mara Untung Ritonga (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze the forms of linguistic politeness and expressive comments in response to posts on the Instagram account "Medantalk" regarding the Pertamina corruption case in February 2025. This study uses Leech's politeness theory in 1983, known as the principle of politeness, and Yule's expressive speech act theory adopted from John Searle in his book entitled Pragmatics in 1996. The method used in this study is descriptive qualitative. The research data are in the form of 72 comments distributed into 5 types of maxims and 4 types of expressive comments. The research findings show that Instagram users apply various forms of linguistic politeness, which include praise, generosity, humility, sympathy, and tact. Furthermore, these comments also contain expressive utterances reflecting emotions such as anger, disappointment, sadness, fear, and hope. The implications of this research emphasize the importance of politeness in commenting to foster mutually respectful relationships among Instagram users.